PHONETICS VS PHONOLOGY - Erkinov Adham Anvatr o'g'li; Umirova Zamira (TADQIQOTLAR, 2025)
ANNOTATION:  This  article  explores  the  fundamental  differences  between phonetics  and  phonology,  two  essential  branches  of  linguistics.  While  phonetics analyzes the physical aspects of speech sounds, phonology investigates their functional and  abstract  roles  within  a  language  system.  Understanding  both  areas  is  vital  for linguists, language teachers, and language learners